Increasing The Taxonomic Accuracy of Remote Sensing Data Using Traditional Pattern Recognition Methods - Alsafar, Alhan (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The most significant outcomes of remote sensing are maps of Land Use and Land Cover (LULC), which can be controlled by a procedure known as image classification. Using image processing methods, we are developing a system in this effort to categorize satellite photos and extract information. Satellite pictures have been classified into usable and unused areas, as well as sub-classifying each class into numerous further classes. Used satellite photos are further divided into residential, commercial, highway, and agricultural areas, while unused images are divided into forest, river, desert, and beach areas. Since K-means classifiers analyze images features and Otsu's approach for multilevel image thresholding is efficient for automatic classification of satellite images, that is the main topic of this research.